Análisis de las técnicas de enseñanza-aprendizaje del docente de la asignatura de física, y el logro de los aprendizajes significativos que se alcanzan con los estudiantes del segundo año de bachillerato general unificado de la unidad educativa del milenio Bernardo Valdivieso, sección vespertina, año 2019. - Conde Andrade, Brayan Eulises (2020)
This research work refers to the analysis of the teaching-learning techniques of the teacher of the physics subject, and the achievement of significant learning that is achieved with the students of the second year of the Unified General Baccalaureate of the Millennium Educational Unit Bernardo Valdivieso, evening section, year 2019. The present research raises the general objective of investigating the teaching-learning techniques applied by the teacher in physics classes and their relationship with the development of significant learning in second-year students of the Unified General Baccalaureate of the Millennium Educational Unit Bernardo Valdivieso section morning, period 2019-2020. For its development, different methods and techniques were used, among which are: the scientific method, the analytical method, the statistical method, and techniques such as the test, which allowed to measure the level of meaningful learning of the students, before and after to apply new teaching techniques. Observation was the technique that allowed us to analyze the teaching-learning process used by the teacher in greater depth. In the results obtained in the research, it is determined that the techniques most used by the teacher are considered traditional, a reality that allowed the application of various workshops with alternative teaching techniques, giving priority to the flipped classroom and the questionnaire. As a result of the application of alternative techniques, knowledge about Newton's Laws was strengthened, and with this it was possible for students to develop their significant learning. Unlike the teacher in the workshops, a constant monitoring of the students' knowledge was carried out, allowing to determine the difficulties they present and thus it is necessary to reinforce them, so that they achieve said learning. 5 Currently there are a wide variety of alternative techniques such as: Design Thinking (The Case method), games, self-learning or social media. However, based on the observation made, it was determined that the best and most appropriate techniques were the flipped classroom techniques and the questionnaire. After the application of these techniques, the students' significant learning level had a substantial improvement, since the general average was higher, compared to the general average of 4.12 / 10 obtained by the students with the teacher's techniques, in the subject of physics.